First in vivo evidence of pituitary adenylate cyclase-activating polypeptide antiviral activity in teleost. Issue 103 (August 2020) - Velázquez, Janet; Pérez, Geysi; Semple, Shawna L.; Rodríguez-Ramos, Tania; Díaz-Rosales, Patricia; Ordás, María del Camino; Lugo, Juana María; Dixon, Brian; Tafalla, Carolina; Estrada, Mario Pablo; Carpio, Yamila
Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a multifunctional neuropeptide belonging to the glucagon/secretin superfamily. In teleost fish, PACAP has been demonstrated to have an immunomodulatory role. Although previous studies have shown that viral/bacterial infections can influence the transcription of PACAP splicing variants and associated receptors in salmonids, the antiviral activity of PACAP has never been studied in teleost. Thus, in the present work, we investigated in vitro the influence of synthetic Clarias gariepinus PACAP-38 on the transcription of genes related to viral immunity using the rainbow trout monocyte/macrophage-like cell line RTS11 as a model. Positive transcriptional modulation of interferon gamma (IFNγ), interferon alpha (FNα1, 2), interleukin 8 (IL-8), Mx and Toll-like receptor 3 (TLR3) genes was found in a dose and time dependent manner. We also explored how a pre-treatment with PACAP could enhance antiviral immune response using poly (I:C) as viral mimic. Interferons and IL-8 transcription levels were enhanced when PACAP was added 24 h previous to poly (I:C) exposure. With these evidences, we tested in vivo how PACAP administration by immersion bath affected the survival of rainbow trout fry to a challenge with viral hemorrhagic septicemia virus (VHSV). After challenge, PACAP-treated fish had increased survival compared to non-treated/challenge fish. Furthermore, PACAP was able to decrease the viral load in spleen/kidney and stimulate the transcription of IFNs and Mx when compared to untreated infected fish. Altogether, the results of this work provide valuable insights regarding the role of teleost PACAP in antiviral immunity and point to a potential application of this peptide to reduce the impact of viral infections in aquaculture. Highlights: PACAP up-regulate genes actively involved in antiviral immunity such as IFNs and Mx. PACAP treatment increased rainbow trout survival in challenge against VHSV. PACAP treatment was able to decrease the viral load in rainbow trout tissues.